Experimental investigation of bimetallic nanoparticles heat transfer characteristics in automotive radiators - Altay Arbak; Azade Attar; Melda Altikatoglu Yapaoz; Mustafa Armağan; Yasar Bulbul; Emir Kasım Demir; Yasin Karagöz (Case Studies in Thermal Engineering, 2023)
Improvement of the thermal properties of coolants used in automobile radiators increases the cooling performance of the engine. Metallic nanoparticle additives generally improve the thermal properties of the coolant. In this study, the heat transfer characteristics of a nanofluid prepared with bimetallic additives (CuO–ZnO) for automotive radiators were experimentally investigated. Experiments were made for four different fluids under constant heating power. These are water-bimetal mixture fluids with 0.1%, 0.2% and 0.3% particulate additives. UA values of the heat exchanger were calculated using the logarithmic temperature difference method and compared for different concentrations. As a result, it was observed that the 0.3% additive ratio had the highest UA value. In addition, with the increase of the bimetallic nanoparticle additive rate, the heat transfer also increases. Finally, an economic analysis was carried out for the use of nanoparticles in the water cooling system for a single cylinder natural gas engine.